Observations on the Food Habits and Distribution of Ratel (Mellivora capensis indica) in Gir, India - Pati, B. P.; Vijayan, S.; Mehra, B. S. (Indian Forester, 2001)
Ratel (Mellivora capensis) is a secretive animal and scanty information is available on this species. In Gir PA the recorded sightings of Ratel were very few. In this study an effort was made to determine its habitat use, dietary constituents. Ratel prefers riverine habitat for foraging (54%). In comparison to Riverine burrows (42%), Ratel prefers undulating dry deciduous patches (58%) as its shelter. Ratel prefers small vertebrates in its diet, in comparison to with fruits and tubers. Very little is known about social structure, reproduction and territoriality etc. Although it was known from various sightings that the animal is primarily solitary (80%) but may be seen in pairs rarely.